Fungal pathogens intercepted in imported germplasm of medicinal and aromatic plants and their quarantine significance (Open Access Journal of Medicinal and Aromatic Plants, 2011)
(Abstract selected from presentation in National Conference on Biodiversity of Medicinal and Aromatic Plants: Collection, Characterization and Utilization, held at Anand, India during November 24-25, 2010) Â International exchange of planting material of medicinal plants germplasm has a significant role in crop improvement programmes as it provides a wide genetic diversity available world wide. However, exchange of the planting material carries an inherent risk of introducing new exotic pathogens/ more virulent races into new areas. Plant quarantine is a government endeavour enforced through legislative measures to regulate the introduction of seeds and planting materials, in order to prevent inadvertent introduction of pests, pathogens and weeds harmful to the agriculture of a country/state/region and if introduced, prevent their establishment and further spread. Â During 1976-2009 more than 15,000 samples of more than 70 medicinal and aromatic plants were imported from 42 countries and 330 samples were found to be infected with 29 fungal pathogens. The major interceptions of quarantine significance included Dendryphion penicillatum (Corda) Fr., the blight pathogen of opium poppy, a destructive seed-borne pathogen and potential mycoherbicide for opium poppy crop. Alternaria zinniae Pape ex. Ellis and Botrytis alli Munn having limited geographical distribution in the country; Fusarium oxysporum Schlecht., known to possess a number of physiological races; B. cinerea Pers. Fr., Botryodiplodia theobromae Pat., Colletotrichum dematium (Pers.) Grove, C. gloeosporioides (Penz.) Sacc., Drechslera sorokiniana (Sacc.) Subram. & Jain, F moniliforme Sheldon, F solani (Mart.) Sacc., Macrophomina phaseolina (Tassi) Goid and Rhizoctonia solani Kuhn etc. having wide host range. Further Alternaria brassicicola (Schw.) Wiltshire and F solani (Mart.) Sacco on non-host crops and Ascochyta sp., A. linicola, A. ricini Groves & Skolko, Curvularia lunata (Wakker) Boedjin, Cercospora traversciana Sacc., D. papaveris, Pestalotia sp. and Phomopsis phaseoli Sacco causing damage of economic significance also were intercepted. Introduction of these exotic pathogens or their more virulent strains along with germplasm could pose a serious threat to the indigenous crops. Interception of such a large number of pathogens signifies the role of quarantine in regulating the safe introduction of plant genetic resources needed for the crop improvement programmes of medicinal and aromatic plants of the country.